Pemberdayaan Ibu-Ibu PKK Lubuk Durian melalui Pelatihan Pembuatan Pestisida Alami untuk Pertanian Ramah Lingkungan - Raisawati, Tatik; Sumarni, Hania; Supriyanti, Yuni Indah (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
This community service program in Lubuk Durian, Kerkap District, North Bengkulu, aimed to enhance the knowledge and skills of PKK women in producing eco-friendly pesticides from papaya leaves and rice washing water. The methods of service applied were counseling and practice.The activities included socialization, training, and practical demonstrations on preparation and application. Papaya leaves contain bioactive compounds such as papain, alkaloids, terpenoids, and flavonoids, effective against leaf-eating insects, while fermented rice washing water serves as a sustainable pest control option from household waste. Seventeen participants showed high enthusiasm in the activity and were able to make natural pesticides from papaya leaves and rice water, and applied the training results in their organic vegetable gardens, successfully reducing insect damage and improving yields. The program supports cost efficiency, reduces chemical residues, and strengthens organic farming practices in the community.